2016
DOI: 10.1080/20469047.2016.1250031
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in a paediatric intensive care unit in Kigali, Rwanda

Abstract: The observed mortality rate was in the range reported in other resource-limited settings. The initial attempt to create and implement a risk of mortality tool for this setting determined a score that could identify those patients at higher risk of mortality. In PICUs in resource-limited settings, the gathering of data and use of severity of illness tools could improve care in a number of ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 44 publications
4
29
0
3
Order By: Relevance
“…A população estudada apresentou distribuição por faixa etária semelhante às demais séries 16,17,18,19,20,21 . Em relação ao diagnóstico admissional, foram observadas divergências nos achados em relação a outros estudos 17,22,23,24,25,26 ; nesses, os principais diagnósticos foram doenças respiratórias e neurológicas, enquanto que, neste estudo, as principais doenças foram infecciosas, seguidas de doenças respiratórias e neurológicas.…”
Section: /9unclassified
See 1 more Smart Citation
“…A população estudada apresentou distribuição por faixa etária semelhante às demais séries 16,17,18,19,20,21 . Em relação ao diagnóstico admissional, foram observadas divergências nos achados em relação a outros estudos 17,22,23,24,25,26 ; nesses, os principais diagnósticos foram doenças respiratórias e neurológicas, enquanto que, neste estudo, as principais doenças foram infecciosas, seguidas de doenças respiratórias e neurológicas.…”
Section: /9unclassified
“…Muitos autores relataram que o escore PRISM superestima 3,16,17,18 a mortalidade e que não apresenta boa calibração e discriminação em populações específicas 19,20,21 . No presente estudo, o PRISM apresentou boa capacidade de calibração e discriminação, apesar de ter subestimado a mortalidade, corroborando com outros estudos 19,20,21,27,28,29,30 .…”
Section: /9unclassified
“…The article by Nyirasafari et al [10] in this issue of Paediatrics and International Child Health, describing mortality in a paediatric intensive care unit in Kigali, Rwanda and highlighting the challenges faced by staff, adds important information to this research area and discusses how the data could be used to improve outcomes. Collecting data even on basic measures to arrive at a score and determine outcomes in paediatric intensive care units (PICU) may result in better adherence to national guidelines [11,12] and can help in comparing units, adjusting for their individual patient populations.…”
mentioning
confidence: 99%
“…Collecting data even on basic measures to arrive at a score and determine outcomes in paediatric intensive care units (PICU) may result in better adherence to national guidelines [11,12] and can help in comparing units, adjusting for their individual patient populations. Severity of illness and risk scores make these comparisons and risk-adjustments more straightforward but the authors, along with others, have found that risk scores developed and validated in high-income settings often need to be changed or modified to be applied in LMIC [10,15]. They created a modified paediatric risk of mortality (PRISM) score which had a range of 0-30 and used only 5 of 17 components of PRISM, with a cut-off at 5 for severity; thus children would have had only one or two components with severely deranged physiology to satisfy the PRISM criteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation